2008
DOI: 10.1002/ejic.200800622
|View full text |Cite
|
Sign up to set email alerts
|

1,2‐Diboracyclopentanes without Strong Donor Substituents: Synthesis, Reactions, and Computational Analysis

Abstract: The 1,2-diduryl-1,2-diboracyclopentane 1a was obtained in good yield from the recently described 1,2-dichloro-1,2-diboracyclopentane 1c. Thermolysis of 1a led to a mixture of compounds from which degradation products 5a and 6a as well as isomer 7a could be isolated. Sterically less-hindered 1b spontaneously transformed into its isomer 7b. Attempts to prepare 4a by deprotonation of 1a led to ring enlarged anions 8a and 8b. The structures of all new compounds were definitively proven by X-ray structural analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…114 The synthesis, reactions and computational analysis of a series of 1,2-diboracyclopentanes have been described. 115 o-(Hydroxydimethylsilyl)(dimesitylboryl)benzene has been shown to undergo intramolecular cyclisation to yield the Si-O-B heterocycle, 5,5-dimesityl-2,2-dimethyl-3,4-benzo-1,2,5-oxasilaboracyclopentene which was characterized by X-ray crystallographic analysis and HF calculations. 116 Reaction of the diazaboroline system (21) with lithium diisopropylamide has been shown to result in the formation of the anionic diazaborolide system (22).…”
Section: Mono- Di-and Trialkyl/aryl Boranes Including Fluorinated Bor...mentioning
confidence: 99%
“…114 The synthesis, reactions and computational analysis of a series of 1,2-diboracyclopentanes have been described. 115 o-(Hydroxydimethylsilyl)(dimesitylboryl)benzene has been shown to undergo intramolecular cyclisation to yield the Si-O-B heterocycle, 5,5-dimesityl-2,2-dimethyl-3,4-benzo-1,2,5-oxasilaboracyclopentene which was characterized by X-ray crystallographic analysis and HF calculations. 116 Reaction of the diazaboroline system (21) with lithium diisopropylamide has been shown to result in the formation of the anionic diazaborolide system (22).…”
Section: Mono- Di-and Trialkyl/aryl Boranes Including Fluorinated Bor...mentioning
confidence: 99%
“…14 Fischer and Power 14 divided known compounds into two classes, neutral complexes of RE=E'R 2 (where E = group 13 element and E'= group 14 element) and monoanionic complexes [R 2 E=E'R 2 ] -. Of the neutral complexes (RE=E'R 2 ), known compounds only include formal boron double bonds with either carbon 19 (4) or silicon 20 (5, Figure 7). In both cases, the boron-carbon and boron-silicon double bonds were identified to be 10% shorter than their respective standard single bonds.…”
Section: Multiple Bonding Between Groups 13 and 14mentioning
confidence: 99%
“…In both cases, the boron-carbon and boron-silicon double bonds were identified to be 10% shorter than their respective standard single bonds. 19,20 In the case of the B-Si complex (5) computational studies identified that there was some resonance bonding with the ring nitrogen that also contributed to the bonding structure. 20 19,20 Examples of the monoanionic complexes ([R 2 E=E'R 2 ] -) are slightly more numerous, the most common type of compounds are boron-carbon complexes, where the boron is considered to be stabilising a carbanion.…”
Section: Multiple Bonding Between Groups 13 and 14mentioning
confidence: 99%
See 2 more Smart Citations